2019
DOI: 10.3892/or.2019.7216
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic values of integrin α subfamily mRNA expression in colon adenocarcinoma

Abstract: The integrin α ( ITGA ) subfamily genes play a fundamental role in various cancers. However, the potential mechanism and application values of ITGA genes in colon adenocarcinoma (COAD) remain elusive. The present study investigated the significance of the expression of ITGA genes in COAD from the perspective of diagnosis and prognosis. A COAD RNA-sequencing dataset was obtained from The Cancer Genome Atlas. The present study investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…The association of ITGα1β1 and the progression of CRC has been reported 24 . The ITGα8 mRNA was reported as a potential diagnostic biomarker whereas ITGα5 may serve as an independent prognosis indicator for CRC 25 . In the CRC cells described herein, the predominant expressions were ITGα5‐subunit in HCT‐116 and ITGβ4‐subunit in HT‐29 cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The association of ITGα1β1 and the progression of CRC has been reported 24 . The ITGα8 mRNA was reported as a potential diagnostic biomarker whereas ITGα5 may serve as an independent prognosis indicator for CRC 25 . In the CRC cells described herein, the predominant expressions were ITGα5‐subunit in HCT‐116 and ITGβ4‐subunit in HT‐29 cells.…”
Section: Discussionmentioning
confidence: 57%
“…24 The ITGα8 mRNA was reported as a potential diagnostic biomarker whereas ITGα5 may serve as an independent prognosis indicator for CRC. 25 In the CRC cells described herein, the predominant expressions were ITGα5-subunit in HCT-116 and and α6β4. 5,19 In the present study,…”
Section: Discussionmentioning
confidence: 76%
“…For example, in colon adenocarcinoma (CAC), COL1A2 , THBS2 , and COL1A1 were related to prognosis [ 20 ]. In addition, it was found that the level of ITGA5 in CAC was significantly linked to overall survival (OS), which might serve as an independent prognostic indicator [ 21 ]. In neuroblastoma, it has been revealed that there existed an association between SDC3 expression and improved prognosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study found that ITGA8 is highly expressed in early recurring myeloma and can be used as a potential marker of multiple myeloma recurrence [ 34 ]. It is also highly expressed in colon cancer tissues [ 35 ]. ITGA8 can also be used to predict the prognosis of clear cell renal cell carcinoma [ 36 ].…”
Section: Discussionmentioning
confidence: 99%